MỤC LỤC
Rút gọn biểu thức $\Large P=\dfrac{{{a}^{\sqrt{3}+1}}.{{a}^{2-\sqrt{3}}}}{{{\left( {{a}^{\sqrt{2}-2}} \right)}^{\sqrt{2}+2}}}$ với $\Large a>0$
Lời giải chi tiết:
Hướng dẫn giải
Ta có $\Large \left\{ \begin{align}& {{a}^{\sqrt{3}+1}}.{{a}^{2-\sqrt{3}}}={{a}^{\sqrt{3}+1+(2-\sqrt{3})}}={{a}^{3}} \\& {{\left( {{a}^{\sqrt{2}-2}} \right)}^{\sqrt{2}+2}}={{a}^{(\sqrt{2}-2)(\sqrt{2}+2)}}={{a}^{2-4}}={{a}^{-2}} \\\end{align} \right.$
$\Large \Rightarrow P=\dfrac{{{a}^{3}}}{{{a}^{-2}}}={{a}^{3-(-2)}}={{a}^{5}}$
Xem thêm các bài tiếp theo bên dưới